Laser for post acne scars with or without growth factors: a comparative clinical trial - Sujana, Lakkireddygari; Ankad, Balachandra S.; Beergouder, Savitha L. (International Journal of Research in Dermatology, 2020)
Background: Treatment of acne scars presents a considerable challenge to dermatologists. But with advent of fractional CO2 (FCO2) laser and platelet-rich plasma (PRP), new avenues can be explored. PRP provides various growth factors, so that the healing of laser-damaged skin is accelerated. The aim of this study was to assess the efficacy and safety of FCO2 laser alone and in combination with PRP in patients with post-acne scars. Methods: Eighty patients with acne scars were counseled and randomly assigned into two groups of 40 each. Group A was treated with FCO2 laser alone, while Group B was treated with FCO2 laser and PRP for 6 months. Primary objective was assessment of efficacy of both treatment modalities. Secondary objective was evaluation of safety of treatments. Results: At the end of 6 months, group A showed about 18% reduction, while group B showed about 33% reduction in acne scars on objective assessment. Patient satisfaction as assessed by subjective assessment was greater in group B than in group A. Duration of erythema, edema and crusting was lesser in group B compared to group A. Conclusions: Combination of FCO2 and PRP was found to be more efficacious as compared to FCO2 laser alone. Combining the treatment modalities can provide a new strategy for treating the post-acne scars.